(untitled) (Publicaciones en Ciencias y Tecnología, 2012)
Talk about software quality implies the need to rely on parameters that should allow to establish the minimal levels that a product of this type must reach in order to be considered of quality. This paper aims to propose an extension of the method GRAY WATCH, specially in the technical processes of Analysis and Design connecting the products obtained to the process of Implementation. The orientation of our proposal consists of using the standard of product quality ISO/IEC 25010, which establishes criteria for the specification of quality requirements of software products, their metrics and evaluation, and includes a quality model composed by characteristics and subcharacteristics. The result of this proposal, adds significant value to the extended method, Allowing to system analysts and Computer professionals to specify the precise activities to be performed to obtain quality requirements. To make this work we have supported our e orts in the Domain Engineering process based in Software Quality named InDoCaS as methodology for the definition of activities and products in the processes of Analysis, Design and Implementation of the Application.